2020
DOI: 10.22365/jpsych.2019.304.291
|View full text |Cite
|
Sign up to set email alerts
|

The diathesis-stress model in the emergence of major psychiatric disorders during military service

Abstract: E xisting evidence and the diathesis-stress model hypothesis suggest that stress as an environmental factor may trigger the onset of psychiatric disorders, such as psychosis spectrum disorders, mood disorders, anxiety disorders, in people with an underlying vulnerability. The purpose of this study was to determine the period of time during military service at which symptomatology of clinical significance is more often developed, considering that stress of service and adaptation to its requirements is common to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The results of our study support the application of the diathesis-stress model, using coping styles ( 14 , 15 ), to pain ( 13 ), as we found that the ability for PI to predict MNR depended on an individual's coping style. In our results, PI and non-beneficial coping styles each individually entailed some level of MNR risk; as expected, soldiers who reported both PI and non-beneficial coping had the greatest MNR risk compared to soldiers reporting neither or one of these factors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of our study support the application of the diathesis-stress model, using coping styles ( 14 , 15 ), to pain ( 13 ), as we found that the ability for PI to predict MNR depended on an individual's coping style. In our results, PI and non-beneficial coping styles each individually entailed some level of MNR risk; as expected, soldiers who reported both PI and non-beneficial coping had the greatest MNR risk compared to soldiers reporting neither or one of these factors.…”
Section: Discussionsupporting
confidence: 83%
“…Responses to pain can also be conceptualized using a broader diathesis-stress model ( 13 ), which is often applied to life stressors and psychopathology ( 14 , 15 ). In the diathesis-stress model, the pathological effect of a stressor is a function of its severity and the individual's capacity to cope with it, both of which dynamically change over time.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we provide a few examples of research findings in line with the diathesis–stress model. As the diathesis–stress model contends that the interplay of hereditary, biological predisposition, and environmental stress results in the development of mental disorders, researchers have hypothesized that during military service the onset of major psychopathology may be precipitated by psychosocial stress, leading to an increase in psychiatric hospitalisations during the first months of the military service period for those with greater sensitivity or a lower stress tolerance [ 16 ]. In a sample of 118 hospitalised subjects starting their military service assessed for the expression of psychopathology, 59.3% of the subjects were diagnosed with an anxiety disorder, especially PTSD, out of the total sample due to traumatic stress exposure, implicating the nature of warfare stress in the increased risk of anxiety and stress disorders.…”
Section: Epidemiology and Models Of Ptsd Developmentmentioning
confidence: 99%
“…Intriguingly, the risk of disorder onset within the first two months and hospitalisation was also higher for psychotic spectrum disorders. As the sample was exposed to similar stress levels, these findings suggest that individuals with psychotic spectrum disorders have increased stress sensitivity [ 16 ].…”
Section: Epidemiology and Models Of Ptsd Developmentmentioning
confidence: 99%
“…Anxiety disorders and posttraumatic stress disorder (PTSD) are best understood as a dynamic interaction of aversive experiences in those with inherent vulnerabilities to develop anxious states (Barlow, 2000;Chasiropoulou et al, 2019). A learning diathesis model accentuates individual differences in associative learning as a final common path to pervasive avoidance (Servatius et al, 2008;Beck et al, 2010;Allen et al, 2019), a core feature of anxiety disorders (Mellick et al, 2019), and PTSD (O'Donnell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%